Determination of the technical parameters of shaping tools for delimbing head - M. Mikleš (Research in Agricultural Engineering, 2012)
It is usually a technical problem to find mathematical ideal shape of knives of delimbing head. Determination of their shape in the form of general curve could lead to the technically unfeasible dimensions of the head. Criterion of the optimal shape of cutting contour of head is tightness of encirclement of cross section of trunk by knives. Research attention was aimed at conics. Parabola is the most suitable curve for achieving the best quality of delimbing.